ANALISIS PENGARUH PENDANAAN DARI LUAR PERUSAHAAN DAN MODAL SENDIRI TERHADAP TINGKAT PROFITABILITAS PADA PERUSAHAAN AUTOMOTIVE AND COMPONENTS YANG GO PUBLIC DI BURSA EFEK INDONESIA - AYU L, RATNA (Jurnal Akuntansi AKUNESA, 2013)
The purpose of this research to determine the effect from outside the company’s financingand equity capital either simultaneously or partially on the level of profitability in theautomotive and components industry sector. Method used in this research is descriptivekuantitative. The analytical method used is multiple linear regression analysis. Partially,based on the test results of this study indicate that the independen variables are outside thecompany’s financing (Current Liabilities and Long Term Liabilities) had no significant effecton the level of profitability, although the shareholder equity had significant effect on the levelof profitability. Simultaneously Current ratio, DER and primary ratio have a significanteffect on the level of profitability.Keywords: current lliabilities, long term liabilities, shareholder equity, ROI.